Penerapan hipnosis lima jari untuk mengelola kecemasan pada remaja menggunakan media booklet “Stay cool, bukan stressful” - Lismayanti, Desty; Sarini, Sarini; Rosmiyanti, Yanti; Fitriani, Dewi Rubi; Asih, Okti Rahayu; Sumitro, Sumitro; Novita, Debi; Sunarti, Sunarti; Seli, Yohana (JOURNAL of Public Health Concerns, 2026)
Background: Anxiety is a common mental health issue among adolescents, particularly among 12th-grade students facing academic demands leading up to exams and preparing for graduation. Promotive and preventive efforts through education and training in simple relaxation methods are essential in schools. Purpose: To increase the knowledge and skills of adolescents in managing anxiety using five finger hypnosis. Method: This community service activity, through counseling and outreach, was held on January 12, 2026, at Sehati Karawang Vocational School, with 55 adolescents from 12th grade participating. The goal of this activity was to manage anxiety using five-finger hypnosis in adolescents. The activity used an interactive communicative approach. Material was delivered through presentations and direct discussions supported by booklets. Knowledge levels were measured using questionnaires and direct interviews administered before and after the educational activity (pre-test) and after the educational activity (post-test). Observation and mentoring activities were conducted with adolescents practicing the five-finger hypnosis therapy independently. Descriptive evaluation is carried out by looking at changes in participants' knowledge and understanding scores before educational activities (pre-test) and after educational activities (post-test). Results: The level of knowledge of respondents regarding anxiety management before the educational activity was 12 (21.8%) in the poor category and 43 (78.2%) in the poor category. There was an increase in the level of knowledge of respondents after the educational activity, with 38 (69.1%) in the good category and 17 (30.9%) in the fair category. Most respondents were able to directly practice five-finger hypnosis therapy and experienced immediate psychological and psychological benefits. Conclusion: Community service activities through the socialization and demonstration of five-finger hypnosis techniques combined with deep breathing relaxation have proven effective in increasing adolescents' understanding and skills in managing anxiety independently. Increased understanding of anxiety and the ability to manage anxiety symptoms with five-finger therapy in adolescents can have a positive psychological impact and foster high self-confidence. Suggestion: It is hoped that this activity can become a sustainable mental health education program. By developing the ability to manage anxiety from adolescence, it is hoped that adolescents can face academic and social demands in a more positive and mentally healthy manner. Keywords: Adolescents; Anxiety; Community service; Five-finger hypnosis; Health education Pendahuluan: Kecemasan merupakan isu kesehatan mental yang sering terjadi pada remaja, terutama di kalangan remaja kelas XII yang akan berhadapan dengan tuntutan akademis menjelang ujian, maupun persiapan setelah lulus. Upaya promotif dan preventif melalui edukasi dan pelatihan metode relaksasi sederhana sangat perlu untuk diterapkan di sekolah. Tujuan: Untuk meningkatkan pengetahuan dan kemampuan remaja dalam mengelola kecemasan menggunakan hipnosis lima jari. Metode: Kegiatan pengadian masyarakat melalui penyuluhan dan sosialisasi ini diselenggarakan pada tanggal 12 Januari 2026 di SMK Sehati Karawang dengan jumlah peserta sebanyak 55 remaja dari kelas XII. Sasaran dalam kegiatan ini adalah tatalaksana pengelolaan kecemasan dengan menggunakan hipnosis 5 jari pada remaja. Kegiatan dilaksanakan dengan pendekatan komunikatif interaktif. Materi disampaikan melalui ceramah presentatif dan diskusi langsung yang dibantu dengan media booklet. Pengukuran tingkat pengetahuan menggunakan kuesioner dengan wawancara langsung yang diberikan sebelun kegiatan edukasi (pre-test) dan sesudah kegiatan edukasi (post-test). Kegiatan observasi dan pendampingan dilakukan pada remaja dalam praktik langsung mengikuti langkah terapi hipnosis lima jari secara mandiri. Evaluasi secara deskriptif dilakukan dengan melihat perubahan nilai pengetahuan dan pemahaman peserta sebelum kegiatan edukasi (pre-test) dan sesudah kegiatan edukasi (post-test). Hasil: Menunjukkan bahwa tingkat pengetahuan responden mengenai pengelolaan kecemasan sebelum kegiatan edukasi adalah sebanyak 12 orang (21.8%) dalam kategori kurang dan sebanyak 43 orang (78.2%) dalam kategori kurang. Terdapat peningkatan tingkat pengetahuan responden setelah kegiatan edukasi menjadi sebanyak 38 orang (69.1%) dalam kategori baik dan sebanyak 17 orang (30.9%) dalam kategori cukup. Sebagian besar responden dapat melakukan praktik langsung terapi hipnosis lima jari dan mendapatkan manfaat secara langsung secara psikologis maupun psikis. Simpulan: Kegiatan pengabdian masyarakat melalui sosialisasi dan demonstrasi teknik hipnosis lima jari dengan kombinasi relaksasi napas dalam terbukti efektif dalam menambah pemahaman serta keterampilan remaja dalam mengelola kecemasan secara mandiri. Meningkatnya pemahaman tentang kecemasan dan kemampuan dalam mengelola gejala kecemasan dengan terapi lima jari pada remaja dapat memberikan dampak positif secara psikologis dan menumbuhkan rasa percaya diri yang tinggi. Saran: Diharapkan kegiatan ini bisa menjadi program pendidikan kesehatan mental secara berkelanjutan. Dengan adanya kemampuan dalam mengelola kecemasan sejak usia remaja, diharapkan remaja dapat menghadapi tuntutan akademis dan sosial melalui cara yang lebh positif dan sehat secara mental.